The Relationship Between Memorizing the Qur'an and Students' Academic Achievement: Case Study of Science Subjects at Tahfidzul Quran An-Nahl Mataram Integrated Islamic Elementary School - Al-Qoyyim, Thufail Mujaddid; Affan, Affan; Maulidiya Nabila, Siti; Muhaini, Muhaini; Hajariah, Siti; Suri, Aida Atika; Buntana, Buntana (Mataram University, 2024)
This research analyses the relationship between memorizing the Al-Qur'an and students' academic achievement in Natural Sciences (IPA) subjects at SD IT Tahfidzul Quran An Nahl. This study uses a quantitative approach with a correlational design to measure the relationship between the amount and quality of memorizing the Al-Qur'an and science learning outcomes for students in grades 4 and 5. The research sample consisted of 27 students who were selected purposively. Data on the amount of memorization was taken from the accumulated results of daily evaluations of Al-Qur'an memorization. In contrast, the quality of memorization was assessed based on tajwid, Maharaj, and fluency. Science learning outcomes were obtained from the final summative assessment of even grades 4 and 5 semesters. Data were analyzed using Pearson's descriptive and correlational statistics. The research results show a positive correlation between the amount of memorization and the quality of memorization and science learning outcomes. These findings indicate that memorizing the Qur'an contributes to students' spiritual development and positively impacts their academic achievement, especially in science subjects. This research provides important insights for developing an integrative curriculum, combining religious and academic education to achieve holistic development of students.